Cloze test pocket worksheet as aid to mastery of science concepts - Adelita Morales Gomba (Intelektual Pustaka Media Utama, 2019)
This study used a Two Groups, Random Selection Experimental Design to improved academic performance of Grade 9 learners of Silanga National High School Catbalogan City using Cloze Test Pocket Worksheet in Science. Its purpose was to seek answers to the following questions: (1) What is the pretest mean scores between the control and experimental group? (2) What is the posttest mean scores of the control and experimental group? (3) What is the mean gain scores of the selected experimental group before and after the conduct of the study? Based on the result, the following findings were formulated; (1) The pretest mean scores of the subjects using Cloze Test Pocket Woksheet and the pretest mean scores of those who did not used do not differ significantly. (2) The post-test means scores of subjects who were were using Cloze Test Pocket Woksheet and the posttest mean scores of the subjects who were not using Cloze Test Pocket Woksheet differ significantly. (3) There is a significant difference between the mean gain scores of the two groups of samples – experimental and control groups. The experimental group who used Cloze Test Pocket Woksheet performed significantly higher than the control group who were not using the Cloze Test Pocket Woksheet. Based on the findings cited, it is concluded that the developed material in reviewing Science can improve learners’ mastery of the concepts. Though the results of this study showed that learning took place in both groups, the subjects who were assessed by Cloze Test Pocket Worksheet performed significantly better than the subjects who did not use the material.